Réponses

Meilleure réponse !
2013-10-24T14:23:37+02:00
A = 7 ( x + 9 )
= 7 * x + 7 * 9
= 7x + 63

B = 6 ( 9y - 8 )
= 6 * 9y + 6 * (-8)
= 54y - 48

C = -5 ( 5 - 7z )
= -5 * 5 + (-5) * (-7z)
= -25 + 35z

D = x ( x - 4 ) + x^2
= x * x + x * (-4) + x^2
= x^2 - 4x + x^2
= 2x^2 - 4x

E = ( y + 1 ) ( y - 2 )
= y * y + y * (-2) + 1 * y + 1 * (-2)
= y^2 - 2y + 1y - 2
= y^2 - 2y - 2

F = ( 2x + 1 ) ( 5 - 3x ) - ( 5x - 1 ) x
= 2x * 5 + 2x * (-3x) + 1 * 5 + 1 * (-3x) - x * 5x + x * (-1)
= 10x - 6x^2 + 5 - 3x - 5x - 1x
= 1x - 6x^2 + 5
  • Utilisateur Brainly
2013-10-24T14:33:30+02:00
Je n'arrive pas à supprimer ma réponse .. Comment fair e?